The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0101-31222007000300018
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de sementes de pau-ferro submetidas a diferentes condições de armazenamento, escarificação química, temperatura e luz

Abstract: RESUMO -Caesalpinia leiostachya (Benth.) Ducke (pau-ferro) é uma planta arbórea nativa do Brasil, cujas sementes possuem dormência causada pela impermeabilidade do tegumento à água. Neste trabalho foram conduzidos dois experimentos, nos quais foram utilizados diferentes períodos de escarificação em ácido sulfúrico concentrado para superar a dormência das sementes. No primeiro experimento, sementes coletadas em agosto de 1997 foram armazenadas por oito meses em ambiente não controlado no interior do próprio fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 5 publications
0
17
0
11
Order By: Relevance
“…In addition, for this treatment, superior results were observed for the germination speed index when compared to the others (Table 1). Biruel et al (2007) observed that the treatments with immersion of C. ferrea seeds in sulfuric acid from 15 to 30 minutes were the most effective for overcoming physical dormancy and, consequently, greater values were observed for germination and GSI. Medeiros Filho et al (2005) and Coelho et al (2010) observed that hot water was not effective for overcoming dormancy of the same species as observed in this study.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, for this treatment, superior results were observed for the germination speed index when compared to the others (Table 1). Biruel et al (2007) observed that the treatments with immersion of C. ferrea seeds in sulfuric acid from 15 to 30 minutes were the most effective for overcoming physical dormancy and, consequently, greater values were observed for germination and GSI. Medeiros Filho et al (2005) and Coelho et al (2010) observed that hot water was not effective for overcoming dormancy of the same species as observed in this study.…”
Section: Resultsmentioning
confidence: 93%
“…There are various studies related to seed analysis in this species (Teixeira et al, 2004;Medeiros Filho et al, 2005;Lima et al, 2006;Biruel et al, 2007;Câmara et al, 2008;Teixeira and Machado, 2008;Coelho et al, 2010). Thus, the aim of this study was to evaluate the physiological, physical, and morpho-anatomical characteristics of the L. ferrea seeds before and after application of different treatments for overcoming dormancy.…”
Section: Introductionmentioning
confidence: 97%
“…Em um teste de germinação preliminar, conduzido a 25 ºC com sementes escarificadas por 30 min (condições recomendadas por BIRUEL et al, 2007), foi comparado o comportamento germinativo de sementes alongadas, separadas pela espessura em achatadas e abauladas, a partir de uma mistura das cinco classes de largura. As sementes achatadas apresentaram baixa capacidade germinativa, em relação às abauladas, e não foram utilizadas nos três experimentos realizados.…”
Section: Methodsunclassified
“…Biruel (2001) verificou que as sementes são encontradas em três formas: alongada, angular e arredondada; as sementes alongadas podem-se apresentar de forma achatada e abaulada, e as angulares geralmente apresentam três extremidades angulares. As sementes apresentam também variação quanto ao tamanho, com comprimento variando de 5 a 10 mm e a largura de 4 a 6 mm (CARVALHO, 2003).…”
Section: R áRvore Viçosa-mg V34 N2 P197-204 2010unclassified
See 1 more Smart Citation